SOLUBLE HLA-G LEVEL EFFECT ON GMZ2 SPECIFIC IgG PRODUCTION AFTER IMMUNISATION. (12th February 2017) - Nouatin, Odilon; Ngoa, Ulysse Ateba; Dejon, Jean Claude; Edoa, Jean R; Homoet, Andreas; Engelhon, Julie Englhon; Massinga-Louembe, Marguerite; Esen, Meral; Theisen, Michael; Sim, Kim Lee; Richie, Thomas; Luty, Adrian Jf; et al.
Abstract : Background: Malaria is a major public health problem particularly in Africa. Despite the relatively good immunogenicity profile of the vaccine candidates in naive population, most of them are poorly immunogenic in malaria endemic population. This could be due to an induction of various immune regulatory mechanisms. It has recently been shown that high levels of an immune regulatory molecule sHLA-G in infants increased the risk of malaria, and question may arise as to whether it can equally impair vaccine induced immune response. In this study we have assessed the correlation between sHLA-G and the immune response induced by GMZ2 a blood stage malaria vaccine candidate. Methods: It was an observational study nested within a phase Ib trial aiming to assess the safety, immunogenicity and efficacy of GMZ2 adjuvanted with CAF01, on fifty Gabonese adults lifelong exposed to Plasmodium spp. Three doses of either the vaccine candidate or Rabies vaccine were injected at Day 0, Day 28, Day 56. Peripheral blood sample was collected at Day 0 and Day 7 after the first vaccine administration as well as 28 days after the third vaccine administration (Day 84). sHLA-G level was measured by ELISA on Day 0 and Day 7, and the anti GMZ2, anti MSP3, Glurp IgG concentrations were determined by ELISA on Day 0, 7 and 84. Vaccine efficacy was assessed using PfSPZ Challenge. Results: sHLA-G level was significantly increased from Day 0 to Day 7 (p=0.004) and correlated with a significant decrease of anti-GMZ2 total IgG (r=–0.35, p=0.04). No correlation was found between sHLAG and anti MSP3, Glurp IgG production. Interestingly, individuals who did not develop malaria after the challenge had a lower level of sHLA-G at baseline (p=0.03). Conclusions: Vaccination with GMZ2 induces an increase of sHLA-G level resulting in a decrease of vaccine immunogenicity. This could have an implication for the design of malaria vaccine candidates in semi-immune individuals.